Implementasi Deep Learning dengan Bantuan AI untuk Meningkatkan Keterampilan Guru Abad 21: Inovasi Pembelajaran di Era Digita - Yalida, Abdi -; Hasanah, Nur; Putriwanti, Putriwanti; Rahnmita, Rahmita (Universitas Negeri Makassar, 2025)
This study is motivated by the limited research on the implementation of Deep Learning based on Artificial Intelligence (AI) in supporting 21st-century teacher competencies, despite the fact that this phenomenon has a significant impact on the quality of learning in elementary schools. The purpose of this study is to analyze the effectiveness of applying Deep Learning supported by AI through the Teachy and Thunkable platforms in improving teacher competencies and student engagement. The method used is mixed methods. The research subjects consisted of 8 teachers and 30 students from SDN Toipan selected using purposive sampling techniques. Data were collected through questionnaires, semi-structured interviews, and observations, then analyzed using descriptive statistics and thematic analysis based on Miles & Huberman’s model. The results showed that teachers responded very positively to the use of AI with an average questionnaire score of 3.75 (strong category), and 90% of students were actively engaged in learning activities using the Thunkable application. These findings support 21st-century learning theory, which emphasizes the importance of mastering 4C skills (critical thinking, creativity, collaboration, and communication). The conclusion of this study is that the integration of AI-based Deep Learning is effective in improving teacher competencies as well as encouraging student engagement, although some teachers still face technical challenges.